G12/13 Signaling Pathways Substitute for Integrin αIIbβ3-Signaling for Thromboxane Generation in Platelets - Bhavaraju, Kamala; Lakhani, Parth R.; Dorsam, Robert T.; Jin, Jianguo; Hitchcock, Ian S.; Sanjay, Archana; Kunapuli, Satya P. (PLOS ONE, 2011)
Background We have previously shown that ADP-induced TXA2 generation requires signaling from αIIbβ3 integrin in platelets. Here we observed that, unlike ADP, protease-activated receptor (PAR)-mediated TXA2 generation occurs independently of αIIbβ3. PAR agonists, but not ADP, activate G12/13 signaling pathways. Hence, we evaluated the role of these pathways in TXA2 generation. Principal Findings Inhibition of ADP-induced thromboxane generation by fibrinogen receptor antagonist SC57101 was rescued by co-stimulation of G12/13 pathways with YFLLRNP. This observation suggested an existence of a common signaling effector downstream of integrins and G12/13 pathways. Hence, we evaluated role of three potential tyrosine kinases; c-Src, Syk and FAK (Focal Adhesion Kinase) that are known to be activated by integrins. c-Src and Syk kinase did not play a role in ADP-induced functional responses in platelets. Selective activation of G12/13 pathways resulted in the activation of FAK, in the absence of integrin signaling. Interestingly, αIIbβ3-mediated FAK activation occurred in a Src family kinase (SFK)-independent manner whereas G12/13 pathway caused FAK activation in a SFK and RhoA-dependent manner. A FAK selective inhibitor TAE-226, blocked TXA2 generation. However, in comparison to WT mice, Pf4-Cre/Fak-Floxed mice did not show any difference in platelet TXA2 generation. Conclusions Therefore, we conclude that differential activation of FAK occurs downstream of Integrins and G12/13 pathways. However, the common effector molecule, possibly a tyrosine kinase downstream of integrins and G12/13 pathways contributing to TXA2 generation in platelets remains elusive.